Solubility of Co2 in piperazine (PZ) activated aqueous solutions of 2- amino-2-methyl-1-propanol (AMP) at elevated pressures - Murshid, G. (Trans Tech Publications Ltd, 2014)
The solubility of carbon dioxide (CO2) was measured in aqueous solutions of 2-amino-2- methyl-1-propanol (AMP) and Piperazine (PZ) activated aqueous solutions of (AMP) at two different temperatures (303.15 and 333.15)K and at various concentrations of studied solvents. The measurements were made over the pressure range of 5 to 60 bar. The results are presented as a function of pressure. It has been found that the addition of PZ to the aqueous solutions gives significantly higher CO2 loadings at higher pressures. The influence of pressure on solubility is found to be positive. However, solubility decreases with the increase of temperature. Â© 2014 Trans Tech Publications, Switzerland.